DESAIN PEMBELAJARAN BERBASIS ICT UNTUK PENGEMBANGAN HUMANITY DAN SUSTAINABILITY EDUCATION - Novita Dwi Nur; Amilatul Fadilah; Riris (PT. Hasba Edukasi Mandiri, 2026)
The advancement of information and communication technology (ICT) has opened new horizons in education, particularly in designing learning environments that extend beyond digital proficiency to integrate humanitarian values and sustainability awareness. This article aims to examine ICT-based instructional design models that support the development of human values and sustainability consciousness among learners. Through a systematic literature review, this study found that ICT integration designed with humanity and sustainability principles significantly enhances student engagement, empathy, and social responsibility. Effective instructional designs encompass collaborative digital platforms, content grounded in environmental and social issues, and project-based reflective assessments. The findings affirm that ICT is not merely a tool, but a medium for cultivating a generation that is principled, globally minded, and committed to sustainable futures.